Cast versus functional brace in the rehabilitation of patients treated for an ankle fracture: protocol for the UK study of ankle injury rehabilitation (AIR) multicentre randomised trial. Issue 12 (18th December 2018) - Kearney, Rebecca Samantha; McKeown, Rebecca; Stevens, Siobhan; Parsons, Nicholas; Parsons, Helen; Wells, Philip; Brown, Jaclyn; Underwood, Martin; Redmond, Anthony; Mason, James; Costa, Matthew L
Abstract : Introduction: Each year in the UK over 120 000 people fracture their ankle. It is not known what the best rehabilitation strategy is for these people. Traditionally standard care has involved immobilisation in a plaster cast but an alternative is a functional brace, which can be removed to allow early movement. This paper details the protocol for a multicentre randomised trial of plaster cast immobilisation versus functional bracing for patients with an ankle fracture. Methods and analysis: We will recruit adults with a fractured ankle, for which the treating clinician would consider plaster cast to be a reasonable management option. Randomisation will be on a 1:1 basis, stratified by centre, operative or non-operative management and age. Participants will be allocated to either plaster cast or a functional brace, both treatments are widely used. To have 90% power to detect a difference of 10 points on the primary outcome (Olerud and Molander Ankle Score) at the primary outcome time point (16 weeks), we need to randomise a minimum of 478 people. Quality of life and resource use will be collected at 6, 10, 16, 24 weeks and 12, 18, 24 months. The differences between treatment groups will be assessed on an intention-to-treat basis. The economic evaluation will adhere to the recommendations of the National Institute for Health and Care Excellence reference case. Ethics, registration and dissemination: National Research Ethic Committee approved this study on 4 July 2017 (17/WM/0239). The first site opened to recruitment 9 October 2017. The results of this trial will be submitted to a peer-reviewed journal and will inform clinical practice. Trial registration number: ISRCTN15537280 ; Pre-results.